Analisis Tingkat Kesehatan Bank Menggunakan Metode Camel (Capital, Asset Quality, Management dan Liquidity): Studi Kasus PT. Bank SulselBar Periode 2016-2021 - Nanda Febry Malangi; Muh. Ikhwan Maulana Haeruddin; Nurman; Anwar Ramli; Andi Mustika Amin (PT Maju Malaqbi Makkarana, 2023)
This study aims to determine the level of bank soundness using the CAMEL method, namely Capital, Asset Quality, Management, Earning and Liquidity at PT. Bank Sulselbar Year 2016-2021. This type of research used is quantitative descriptive research. The data used is secondary data and uses data collection methods, namely documentation. The results showed that the soundness level of the Sulselbar bank for 6 years, namely 2016-2021, was included in the HEALTHY category in accordance with the applicable standards in terms of the CAMEL ratio.